STUDI TENTANG ANALISIS REAKSI PASAR DAN RISIKO INVESTASI PADA PERUSAHAAN MANUFAKTUR YANG MELAKUKAN MANAJEMEN LABA: STUDI DI BURSA EFEK INDONESIA - Sjafrudin Redjab; Budi Santoso; Nur Fitriah (Universitas Trunojoyo Madura, 2016)
This research is aimed to analyze the differences and differences in the risk of market reaction investments in companies that perform earnings management measures with the trend of income increasing and income decreasing . Research carried out by the analysis of earnings management action relationship with cummulative Abnormal Return (CAR) as well as the risk of investment in manufacturing companies listed on the Stock Exchange. The main data collection with the technical documentation of the data held by the Stock Exchange in the form of Indonesian Capital Market Directory (ICMD) and www.idx.co.id. The analysis tool uses the calculation of CAR, investment risks, Eckel Index, Kolmogorov-Smirnov test, test and test different significance correlation t.The results of this research found that the actions of the agency earning management with profit increasing trend (income increasing and a decrease in net earnings (income decreasing does not affect the market reaction, as well as risks associated with the market. Different test management measures the return on the market's reaction and the risk of investment shows that acceptable testing criteria is Ho. Based on the analysis of the significance of the relationship on the action with the market reaction to earnings management and investment risk also proved influential.